2020
DOI: 10.1101/2020.05.04.20090688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Covid-19 Dynamics: A Heterogeneous Model

Abstract: The ongoing Coronavirus disease 2019 (COVID-19) epidemic is different from the previous epidemic of severe acute respiratory syndrome (SARS), which demands a rigorous analysis for the selection of anti-epidemic measures and their lifting when the epidemic subsides. Here we estimate the basic reproductive number for COVID-19 and propose a dynamical model for the time course of infection number. With this model, we assessed the effects of different measures for infection risk control. The model is different from… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…In addition, many scholars have also discussed different models. Andrey Gerasimov, Georgy Lebedev, Mikhail Lebedev and Irina Semenycheva proposed a heterogeneous model [13] on May 7, 2020 to assess the effects of different measures for infection risk control. They found that after this heterogeneity is incorporated in the model, several characteristics of the epidemic are estimated more accurately.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, many scholars have also discussed different models. Andrey Gerasimov, Georgy Lebedev, Mikhail Lebedev and Irina Semenycheva proposed a heterogeneous model [13] on May 7, 2020 to assess the effects of different measures for infection risk control. They found that after this heterogeneity is incorporated in the model, several characteristics of the epidemic are estimated more accurately.…”
Section: Related Workmentioning
confidence: 99%
“…COVID-19 infection has a heterogeneous disease course; it may be asymptomatic or causes only mild symptoms in the majority of the cases (Gerasimov et al, 2020), while immunologic complications such as macrophage activation syndrome also known as secondary hem phagocytic lymphohistiocytosis, resulting in cytokine storm syndrome and acute respiratory distress syndrome, may also occur in some patients (Hu et al, 2021). The immune system is there to help us fight infection, but sometimes it wreaks more havoc than the disease itself.…”
Section: Introductionmentioning
confidence: 99%